2019
DOI: 10.2147/ndt.s205033
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antidepressant, anti-inflammatory, and antioxidant effects of electroacupuncture through sonic hedgehog–signaling pathway in a rat model of poststroke depression</p>

Abstract: Background: Poststroke depression (PSD) is the most frequent psychological sequela after stroke. Electroacupuncture (EA) treatment is effective for PSD. The study aimed at clarifying the mechanisms of EA’s antidepressant effects in a PSD rat model. Methods: We used middle cerebral artery occlusion to establish the rat model of PSD. Tests of sucrose preference and locomotor activity were performed to examine depressive-like behaviors. We measured malondialdehyde, GSH, SOD, IL6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
5
16
0
Order By: Relevance
“…Of these studies, 11 assessed the effect of EA on depression-related behavior, including performance in the forced swim test (FST), open-field test (OFT), Morris water maze (MWM) test, and sucrose preference test (SPT), and body weight [ 20 , 21 , 23 , 24 , 27 , 29 , 34 , 42 45 ]. Four other studies assessed changes in neuropeptides and neurotransmitters, including the protein and mRNA expression of galanin (Gal) and tryptophan hydroxylase (TPH), and serotonin (5-HT) levels [ 21 , 25 , 30 , 45 ]. Three additional studies assessed changes in hippocampal synaptic plasticity [ 21 , 22 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these studies, 11 assessed the effect of EA on depression-related behavior, including performance in the forced swim test (FST), open-field test (OFT), Morris water maze (MWM) test, and sucrose preference test (SPT), and body weight [ 20 , 21 , 23 , 24 , 27 , 29 , 34 , 42 45 ]. Four other studies assessed changes in neuropeptides and neurotransmitters, including the protein and mRNA expression of galanin (Gal) and tryptophan hydroxylase (TPH), and serotonin (5-HT) levels [ 21 , 25 , 30 , 45 ]. Three additional studies assessed changes in hippocampal synaptic plasticity [ 21 , 22 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 2 studies assessed changes in proinflammatory cytokine levels [ 26 , 40 ], and 2 studies assessed changes in the hypothalamic-pituitary-adrenal (HPA) axis [ 26 , 40 ]. Three other studies assessed changes in BDNF levels [ 27 , 36 , 46 ], while 6 studies evaluated the effects of EA on signaling pathways, including the AC-cAMP-PKA, Shh, extracellular regulated protein kinase (ERK), and mitogen-activated protein kinase (MAPK) signaling pathways, and dopaminergic synapses [ 28 , 31 , 32 , 39 , 41 , 45 ]. The final 2 studies investigated changes in the expression of multiple genes after EA therapy in depressed rats [ 37 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EA therapy can significantly decrease the content of lipid peroxidation end-product malondialdehye (MDA) and 4-hydroxynonenal (4-HNE) in cerebral I/R injury rats [ 60 62 ], possibly via increasing the activities of antioxidative enzymes, namely GSH-Px and SOD [ 63 – 66 ]. In addition, the ginger pharma acupuncture or laser acupuncture can significantly reduce MDA production in the cerebral cortex and hippocampus while increasing catalase, GSH-Px, and SOD simultaneously [ 67 , 68 ].…”
Section: Acupuncture Regulates Oxidative Stress In Ischemic Strokementioning
confidence: 99%
“…Studies have shown that electroacupuncture (EA) treatment is effective for post‐stroke depression (PSD). The mechanism of EA to treat PSD is to suppress inflammation and oxidative stress through activation of the Shh‐signalling pathway 103 . Studies have shown that naringenin via Sonic hedgehog‐Gli1 cell signalling pathway has antidepressant and neuroprotective effects 104 .…”
Section: Effect Of Shh Signal Pathway On Cnsmentioning
confidence: 99%